A survey of Semantic Web Services formalisms. (21st May 2015) - Wang, Hai H.; Gibbins, Nick; Payne, Terry; Patelli, Alina; Wang, Yangang; Orgun, Mehmet A.; Orgun, Atilla Elçi; Pieprzyk, Josef; Chefranov, Alexander; Shankaran, Rajan; Wang, Huaxiong; Zhuge, Hai
Summary The field of Semantic Web Services (SWS) has been recognized as one of the most promising areas of emergent research within the Semantic Web initiative, exhibiting an extensive commercial potential and attracting significant attention from both industry and the research community. Currently, there exist several different frameworks and languages for formally describing a Web Service: Web Ontology Language for Services (OWL‐S), Web Service Modelling Ontology (WSMO) and Semantic Annotations for the Web Services Description Language (SAWSDL) are the most important approaches. To the inexperienced user, choosing the appropriate platform for a specific SWS application may prove to be challenging, given a lack of clear separation between the ideas promoted by the associated research communities. In this paper, we systematically compare OWL‐S, WSMO and SAWSDL from various standpoints, namely, that of the service requester and provider as well as the broker‐based view. The comparison is meant to help users to better understand the strengths and limitations of these different approaches to formalizing SWS, and to choose the most suitable solution for a given application. Copyright © 2015 John Wiley & Sons, Ltd.